RESEARCH OF VIBRATION DISTRIBUTION IN VEHICLE CONSTRUCTIVE (Perner's Contacts, 2012)
The article provides a discussion on the studies comprising active experiments conducted on selected structural elements of vehicles, the purpose of which was to analyze the vibration propagation in vehicles construction. The vibration excitation was achieved by applying an engine working on idle gear. The studies were conducted on vibration propagation for different constant rotational velocity. The changes of the signals were observed in time, frequency and simultaneously in timefrequency domains.